Mitogen-activated protein kinase cascades in Vitis vinifera - ÇAKIR, Birsen; Kılıçkaya, Ozan (Frontiers in Plant Science, 2015)
Protein phosphorylation is one of the most important mechanisms to control cellular functions in response to external and endogenous signals. Mitogen-activated protein kinases (MAPK) are universal signaling molecules in eukaryotes that mediate the intracellular transmission of extracellular signals resulting in the induction of appropriate cellular responses. MAPK cascades are composed of four protein kinase modules: MAPKKK kinases (MAPKKKKs), MAPKK kinases (MAPKKKs), MAPK kinases (MAPKKs) and MAPKs. In plants, MAPKs are activated in response to abiotic stresses, wounding, and hormones, and during plant pathogen interactions and cell division. In this report, we performed a complete inventory of MAPK cascades genes in Vitis vinifera, the whole genome of which has been sequenced. By comparison with MAPK, MAPK kinases, MAPK kinase kinases and MAPK kinase kinase kinase kinase members of Arabidopsis thaliana, we revealed the existence of 14 MAPKs, 5 MAPKKs, 62 MAPKKKs, and 7 MAPKKKKs in Vitis vinifera. We identified orthologs of V. vinifera putative MAPKs in different species, and ESTs corresponding to members of MAPK cascades in various tissues. This work represents the first complete inventory of MAPK cascades in V. vinifera and could help elucidate the biological and physiological functions of these proteins in V. vinifera.